Chiral Copper(II) bis(oxazoline) complexes directly coordinated to amine-functionalized phenylene/biphenylene periodic mesoporous organosilicas as heterogeneous catalysts - Carneiro, Liliana (2016)
Copper(II) complexes with commercial chiral bis(oxazoline)s were for the first time directly coordinated onto amine-modified mesoporous phenylene and biphenylene silicas. All final materials maintained the 2D ordered mesoporous structure. The copper metal coordinates directly to the amine groups within the walls of the materials. The materials were tested as asymmetric heterogeneous catalysts in the kinetic resolution of hydrobenzoin. They were active, selective, and enantioselective in this reaction. The material containing the (S)-(–)-2,2′-isopropylidene-bis(4-phenyl-2-oxazoline) (Me2PhBox) ligand, the best ligand in the homogeneous phase, presented the highest enantioselectivity of all the materials in the first cycle (73 %). The 2,2′-methylenebis[(4S)-4-phenyl-2-oxazoline] (PhBox) ligand rendered the catalyst more stable, independent of the anion or organic moiety in the periodic mesoporous organosilica material; this catalyst was reused over five cycles without any significant loss of catalytic activity or enantioselectivity. This type of ligand plays an important role in the stability of the corresponding copper(II) complex upon immobilization and in the robustness of the heterogeneous catalyst upon reuse.